Clinical impact of skin autofluorescence on high-sensitivity troponin T in hypertensive patients - Takashi Hitsumoto (BMC, 2017)
Abstract Background Recent studies have reported the importance of high-sensitivity troponin T (hs-cTnT) or skin autofluorescence (AF) as a cardiovascular risk factor. However, little is known about the relationship between these two markers. The aim of this study was to clarify the clinical impact of skin AF on hs-cTnT in hypertensive patients, from the perspective of primary prevention of cardiovascular events. Methods In total, 457 outpatients on treatment for hypertension [182 men and 275 women; mean (± SD) age, 67 ± 13 y] and with no history of cardiovascular events were enrolled. Hs-cTnT levels and skin AF were measured using commercial devices, and relationships between hs-cTnT levels and various clinical parameters including skin AF were examined. Results Hs-cTnT was detected in 405 (88.6%) patients. Skin AF was significantly higher in patients with detectable hs-cTnT than in those without detectable hs-cTnT [2.6 ± 0.5 arbitrary units (AU) vs. 2.2 ± 0.5 AU, respectively, p < 0.001]. In patients with detectable hs-cTnT, there was a significantly positive correlation between skin AF and Log-hs-cTnT (r = 0.41, p < 0.001). Furthermore, multiple regression analysis revealed that skin AF was the strongest variable associated with Log-hs-cTnT as a subordinate factor (β = 0.30, p < 0.001). Conclusions The results of this study indicate that skin AF is an important determining factor for hs-cTnT elevation in hypertensive patients with no history of cardiovascular events.